PWE-009 Evaluation of out-of-hours emergency endoscopy outcomes at a large liver and gastrointestinal centre. (22nd June 2015) - Hawken, J; Audimoolam, V; Hayee, B; Dubois, P; Chung-Faye, G; Bjarnason, I; Devlin, J; Harrison, P; Heneghan, M; Agarwal, K; Suddle, A
Abstract : Introduction: Acute Upper GI bleeding is a common medical emergency and is associated with high mortality. Pre-existing co-morbidities along with in-hospital and portal hypertensive bleeds have been linked with increased mortality. With the emphasis and implementation of 24/7 endoscopy cover for gastrointestinal bleeding across the country, we conducted a study into emergency out-of-hours endoscopies to describe patient characteristics, diagnoses and mortality. Method: Retrospective data was collected from all out-of-hours emergency endoscopies at king–s College Hospital, a tertiary referral centre, between 6/10/13 and 2/11/14. The majority of procedures were carried out under general anaesthesia by the on-call endoscopy team in theatre or one of the intensive therapy units (ITU). Referral to endoscopy time, re-bleed rate, completed Rockall score, consequent surgical or radiological intervention and mortality at 72 h and 28 days were collected. Results: 131 endoscopies (mean age 56.2 yrs, 44% >theatre and 53% >ITU), 45% new admissions and 55% in- patients were undertaken. 53% had liver disease as their primary source of morbidity. Variceal bleed was the most common finding (40%), followed by peptic ulcers (24.6%). The mean referral to scope time was 7.7 h (range 2–24) and the 72-hour re-bleed rate was 7.4%. Banding alone or as a combination with histoacryl glue injection was the most frequently used therapy (30%). Mortality with a completed Rockall score of ≤3 was 0%, rising to 39% with a score of ≥7. 72 h and 28 days mortality was 5.8% and 26.7%. Overall 28-day mortality for an out of hospital bleed was 22% and 39% for in hospital bleed. Mortality for variceal bleeding and ulcer bleeding was comparable at 33% and 34%. 2.7% underwent surgery following initial endoscopy and 0.9% interventional radiology. Conclusion: In-hospital bleeds carry high rates of mortality due to extensive comorbidities, especially in the case of liver disease. The study findings of a similarly high mortality for bleeding ulcers as for variceal bleeding in an intensive therapy setting reflects the severity of their critical illness. The high percentage of liver disease patients and those with concurrent critical illness, as well as the fact that the endoscopies were performed out of hours reflecting the clinical urgency, contributes to the higher mortality rate than the 10–14% previously described. Disclosure of interest: None Declared. References: Hearnshaw SA, et al . Acute upper GI bleeding in the UK: patient characteristics, diagnoses and outcomes in the 2007 UK audit. Gut . 2011. doi:10.1136/gut.2010.228437 Rockall TA, et al . Risk assessment after acute upper gastrointestinal haemorrhage. Gut . 1996;38 :316–321